TINDAK TUTUR ILOKUSI PADA KUMPULAN CERPEN SENYUM KARYAMIN KARYA AHMAD TOHARI - Haryati Haryati; Auzar Auzar; Charlina Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is titled Illocutionary Speech Act On A Collection Of Short Stories Karyamin’s Smile By Ahmad Tohari. The purpose of this research is to describe (1) illocutionary language acts on a collection of short stories Karyamin’s Smile by Ahmad Tohari; (2) function illocutionary speech act on a collection of short stories karyamin’s smile by Ahmad Tohari. This type of research is descriptive research, ie solving existing problems based on existing data. Sources of data in this study are the pronunciation interpersonal words on a collection of short stories Karyamin’s Smile by Ahmad Tohari. Data analyzed using Miles and Huberman model by reducing data, present the data, and draw a conclusion from the research. Based on the research, it is found that 65 illocutionary language act consisting of the form of illocutionary language acts assertive, directive, commissive, expressive and declarative. The details of this information (1) the form of illocutionary assertive language acts are 27 expression; (2) the form of a directive illocutionary language sentences number 29; (3) form commissive illocutionary language expression was 6; (4) form illocutionary speech deeds expressive speech was 2; and (5) a declarative illocutionary language act was 1 speech. In this research also found the function of the act of speech illocution consisting of competitive, convivial, and collaborative functions. Competitive function found 29 speeches, convivial 8 speech, and collaborative 28 speech.Key Words: form of illocution, function of illocution, Karyamin’s Smile